Mixture-Based Heterocyclic Combinatorial Positional Scanning Libraries: Discovery of Bicyclic Guanidines Having Potent Antifungal Activities against Candida albicans and Cryptococcus neoformans - Blondelle, Sylvie E. (American Society for Microbiology, 1999)
A mixture-based synthetic combinatorial library of more than 100,000 bicyclic guanidines was generated in a positional scanning format and assayed for activity against Candida albicans. Potent individual bicyclic guanidines were directly identified following the screening of the library. Time-kill curve studies indicated bactericidal activities for the individual bicyclic guanidines. These compounds also showed potent activity against Cryptococcus neoformans. These studies demonstrate the value of using mixture-based combinatorial positional scanning libraries made up of heterocyclic compounds for the rapid identification of novel classes of antifungal compounds.